Sharia Law and Financial Reporting Practices: An Empirical Study of Selected Business Organizations in Gusau Metropolis, Zamfara State, Nigeria - Bamidele, Vincent Olawale (Yayasan Darussalam Patalassang, 2025)
This study empirically investigates the effect of Sharia law on financial reporting practices among selected business organizations in Gusau metropolis, Zamfara State, Nigeria. The research addresses a critical gap in the literature by focusing on local, non-banking businesses in a region where Sharia law is formally integrated into the legal and regulatory framework. Using a descriptive survey design, primary data were collected from 120 business organizations through a structured questionnaire, and analyzed using SPSS version 18. The results reveal that Sharia compliance is a significant positive predictor of both the content and structure (B = 0.48, p < 0.001) and the transparency (B = 0.52, p < 0.001) of financial statements. Disclosure practices also significantly enhance financial statement quality (B = 0.32, p = 0.004) and transparency (B = 0.37, p = 0.001), while reporting challenges negatively affect transparency (B = -0.18, p = 0.027). Perceived benefits are positively associated with Sharia compliance in financial reporting (B = 0.41, p = 0.001). The regression models demonstrated good fit, with R² values ranging from 0.27 to 0.54, and all ANOVA results were statistically significant (p < 0.001). The study concludes that robust Sharia compliance and disclosure practices are pivotal for high-quality, transparent financial reporting, but practical challenges remain. It recommends the development of standardized Sharia-compliant reporting guidelines and targeted professional training to further enhance financial transparency and accountability in Zamfara State and similar contexts.